Dynamic spectrum allocation for cognitive radio sensor networks based on improved genetic algorithm - Chang CAI; Yafang WANG; Bingmei MIAO; Hui JIANG (Dianxin kexue)
ISM (industrial scientific and medical) bands where wireless sensor network works faced with the shortage of spectrum resources problems.Aimed at this case,dynamic spectrum allocation in cognitive radio technology was applied in wireless sensor network.A dynamic frequency spectrum allocation scheme was proposed.The algorithm was a modified adaptive genetic algorithm which was based on graph coloring model.In addition,the objective functions of the algorithm were maximum bandwidth gains and minimum spectrum handoff,besides,in the crossover and mutation process,adaptive crossover probability and mutation probability was used instead of the fixed.Experimental results confirm that compared with the traditional genetic algorithm and color sensitive graph coloring algorithm,the proposed algorithm can achieve the expected goal of improving the spectral efficiency and reducing energy consumption.